KLAUSA KONSESIF DALAM KALIMAT MAJEMUK BERTINGKAT BAHASA INDONESIA - Sumiyanto Sumiyanto; Mukhlish Mukhlish (CARAKA, 2015)
The purposes of this research are (1) to describe the kinds of conjunctions of conses clauses in complex sentences of Indonesian, (2) to describe the structures of syntactic function of conses clauses in complex sentences of Indonesian, (3) to describe the syntactic categories of predicate filler of conses clauses in complex sentences of Indonesian, (4) to describe the dissipation of syntactic function that happened on conses clauses in complex sentences of Indonesian. This type of research is qualitative. The method used in data preparation is listening through note technique. The data analysis method used is an attributable method that includes direct elements techniques, change technique, expand techniques, and insertion techniques. The result presentation method of data analysis in this research is done with formal and informal methods. The research results of conses clauses in complex sentences of Indonesian are as follows. (1) The kinds of conjunctions on konsesif clauses in complex sentences are meski(pun), walau(pun), kendati(pun), sekalipun, betapapun, biarpun, apa pun, and ke mana pun. (2) The structures of syntactic function of conses clauses in complex sentences of Indonesian are (a) = … Ket                                                ,  (b) = … Ket                      ,                             Konj Kons+S+P(+O)(+Pel)(+Ket)               Konj Kons+S+Ødan (c) = … Ket                                     .   (3) The syntactic categories of predicate filler           Konj Kons+Ø+P(+O)(+Pel)of conses clauses in complex sentences of Indonesian include (a) the conses clauses of the verbal predicate,(b) the conses clauses of the adjectival predicate, (c) the conses clauses of the nominal predicate, (d) the conses clauses of the numeral predicate, and the conses clauses of a prepositional phrase. (4) The dissipation of syntactic functions that happened on conses clauses in complex sentences of Indonesian is subject and predicate dissipation.